Kekerabatan sebagai Pranata Sosial yang Mempengaruhi Agency Perlawanan Masyarakat: Studi Kasus Protes Petani terhadap Proyek Pembangunan Irigasi di Sumatra Barat - Popy Dwi Patrojani; Suraya Afiff (Antropologi Indonesia, 2018)
Studies have shown the importance of identity politics in the ability for small-holders to form a solidarity in a collective action protest against development project. However, those studies do not show how the kinship relations in the context of adat system could shape the agency of small-holder to organize collective resistance against the development project that affects their livelihoods. Although we are not denying the importance of traditional kinship relations in developing solidarity among agrarian communities in Indonesia to carry out a public protest, kinship relations system might also be used by other interest such as government, contractor, and traditional leader for shaping some forms of resistance action. Drawing from ethnographic study of the small-holders protests against a governmental irrigation project in West Sumatera, we attempt to show how social relations in the traditional kinship system have significantly shaped their ability to carry out open public protest and gain collective support. Small-holder ability to act need to be analyzed in the complex power relations dynamic among actors involved who are embedded in the traditional kinship relationships that were practiced. Small-holders agency of resistance was hindered by the government and project contractor strategy to incorporate the key traditional leaders into the project.